PEMANFAATAN E-LEARNING SEBAGAI MEDIA EVALUASI PEMBELAJARAN BAHASA ARAB DI MAN 3 HULU SUNGAI SELATAN KALIMANTAN SELATAN - Damar Gemilang (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
Abstract                       Teaching and learning activities are formal activities, therefore an evaluation must be carried out even in a pandemic situation. One of the media that can be used by Arabic language teachers at MAN 3 Hulu Sungai Selatan in conducting evaluations for students is using e-learning. This study aims to determine the use of e-learning in MAN 3 Hulu SungaI Selatan as a medium for evaluating Arabic learning.                       The research design uses the form of research and development (R&D). This research is a qualitative research design with research and development to produce certain products, and to test the effectiveness of these products.                       The results of this research are E-learning is a web-based education system that uses internet facilities and electronic media to operate it, which is useful for facilitating educational activities. Based on its type, e-learning consists of instructor-led, learner-led, embedded e-learning, facilitated, e-coaching and telementoring. The benefits of e-learning are for educators, giving a positive impact on educators in carrying out their obligations in the world of education. For students, students can easily use study materials any time in repeating the subject. Students also can interact with the teacher any time, when the e-learning is accessed. The advantages of e-learning that can be accessed anywhere and anytime and the website pages can be used via PC, laptop or smartphone. The shortcomings of e-learning include reducing the intensity of communication and face-to-face between teachers and students as well as students and students, and teachers are required to further explore or master the learning system using electronic-based learning. Learning Arabic at MAN 3 Hulu Sungai Selatan Kalimantan Selatan uses e-learning media in the form of E-Learning MAN 3 Hulu Sungai Selatan. The purpose of e-learning is to make it easier for students to access evaluation questions in learning Arabic in an interesting way and at the same time being able to see feedback from the teacher to find out learning outcomes.